Characterization of the complete chloroplast genome of Platycladus orientalis (Cupressaceae), an herb to treat lumbar tuberculosis in China. Issue 1 (2nd January 2020) - Fei, Jun; Shi, Shiyuan; Zu, Gang; Han, Guihe; Lai, Zhen; Cao, Tianyi
Abstract: Platycladus orientalis belongs to the family Cupressaceae that the branches and leaves is an important Traditional Chinese Medicine in China. In this article, the complete chloroplast genome of P. orientalis was studied and illustrated to add the more genetic information. The chloroplast genome of Platycladus orientalis is 1127, 113 bp in length as the circular, which exhibits 120 genes, including 83 protein-coding genes (PCG), 33 transfer RNA genes (tRNAs) and 4 ribosomal RNA genes (rRNAs). The overall nucleotide composition of chloroplast genome is: 32.1% of A, 33.2% of T, 17.9% of C, 16.8% of G and the total AT content of 65.3% and GC of 34.7%. Phylogenetic relationship shown that Platycladus orientalis is more closely related to Thuja standishii on genetic relationship using the Maximum-Likelihood (ML) method. The chloroplast genome may contribute to the medicinal valuable and evolutionary studies of this species.